The role of the ruling elites in exacerbating ethnic, denominational discrimination and its Impact on the emergence of social movement in the second wave of the Arab Spring in Sudan - Ezzaghari, Farida (Arab Journal for Sciences and Research Publishing, 2024)
This paper examines the programs and behaviours espoused by the ruling elite in Sudan ahead and during the Arab Spring to maintain their power. It does so by furnishing a deep analysis of the part of the ruling elite in dividing Sudan along ethnical and Denominational lines to save their position. The elite have exploited the country’s ethnical and insular identity to serve their own interests, frequently at the expenditure of weakening public identity. The paper also addresses the part of the failed state in the spread of suppression and serious violations, as well as political, profitable, artistic, and ethnical demarcation. The study, using a donation and analysis methodology, examines the strategic use of ethnical and denominational demarcation by the ruling elite to immortalize their power. It also explores how the performing ethnical and denominational conflicts played a major part in Sudan’s decline. Sudan, with its qualifications and abundant natural coffers, was supposed to be among the Advanced state, but internal divisions have impeded its progress. In other words, the study shows the significance of strengthening a participated public identity as a medium for achieving reform and prostrating internal divisions in Sudan in order to promote public concinnity.